How to access, retrieve and use United Nations Documentation an interactive training tool - United Nations Institute for Training and Research (Geneva: United Nations, 2006)
Includes opening statment in video form (Duration 6:40 minutes) by M r. Marcel A. Boisard, United nations Assistant Secretary-general and Ex ecutive Director of UNITAR.
This CD-ROM was produced by the Multilateral Diplomacy and Internati onal affairs Management Programme of the United Nations Institute for T raining and Research (UNITAR) in collaboration with United Nations Dag Hammarskjold Library in New York, the Library of the United Nations Off ice at Geneva (UNOG) and the UNOG Conference Services.
Minimum configuration required: Pentium processor and 4x speed CD-RO M drive.
Keywords: Information storage and retrieval systems -- United Nations